Establishing school bus baseline emergency evacuation times for elementary school students. (November 2016) - Abulhassan, Yousif; Davis, Jerry; Sesek, Richard; Gallagher, Sean; Schall, Mark
Highlights: Identifying factors that affect school bus egress by full-scale evacuation trials. Child age has a statistically significant effect on bus evacuation time. Egress rates did not statistically change with driver assisted evacuation trials. Evacuation routes used had a statistically significant effect on egress rate. Abstract: Emergency evacuation systems are critical to mass transportation vehicles such as school buses. Previous bus fire propagation tests indicate that the available time for successful evacuation is approximately 3–5 min. Many school districts in the United States utilize school bus routes that exclusively transport children in kindergarten through second/third grade where the bus driver is the only adult onboard. Currently, no standards specify the maximum allowable evacuation time for school buses. Full-scale evacuation trials were performed to measure front door, rear door, and both door (simultaneous) evacuation flow rates for kindergarten through third grade students. The evacuation trials indicated that the grade level of school bus passengers, and available evacuation routes have a significant effect on flow rate ( p < 0.05 ). For evacuation trials with driver's assistance mean flow rate through the front door was 29 children/min, 21 children/min for the rear emergency door, and 36 children/min for evacuations using both doors simultaneously.